CRMP2 and CRMP4 Are Differentially Required for Axon Guidance and Growth in Zebrafish Retinal Neurons - Zhi-Zhi Liu; Jian Zhu; Chang-Ling Wang; Xin Wang; Ying-Ying Han; Ling-Yan Liu; Hong A. Xu (Neural Plasticity)
Axons are directed to their correct targets by guidance cues during neurodevelopment. Many axon guidance cues have been discovered; however, much less known is about how the growth cones transduce the extracellular guidance cues to intracellular responses. Collapsin response mediator proteins (CRMPs) are a family of intracellular proteins that have been found to mediate growth cone behavior in vitro; however, their roles in vivo in axon development are much less explored. In zebrafish embryos, we find that CRMP2 and CRMP4 are expressed in the retinal ganglion cell layer when retinal axons are crossing the midline. Knocking down CRMP2 causes reduced elongation and premature termination of the retinal axons, while knocking down CRMP4 results in ipsilateral misprojections of retinal axons that would normally project to the contralateral brain. Furthermore, CRMP4 synchronizes with neuropilin 1 in retinal axon guidance, suggesting that CRMP4 might mediate the semaphorin/neuropilin signaling pathway. These results demonstrate that CRMP2 and CRMP4 function differentially in axon development in vivo.